A multifunctional additive for adhesive and preparation method thereof

By using zinc-based chitosan sustained release particles, deodorant and antibacterial agents in adhesives, the problem of antibacterial, anti-mold and TVOC removal in existing adhesives is solved, and a safe and environmentally friendly long-term effect is achieved Effect.

CN117126624BActive Publication Date: 2025-02-11CHENGDU TIANYOU JINGCHUANG TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311097795.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-02-11
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

The antibacterial, anti-mold and TVOC removal additives in existing adhesives have a short effective time, and some decomposition products are toxic, which is not conducive to long-term contact of humans.

Method used

Using zinc-based chitosan sustained release particles, deodorants and antibacterial agents, the grafting of aldehyde-based cyclodextrin and chitosan and reacting with soluble zinc salts to form a stable inclusion compound. Improve the release stability of zinc ions.

Benefits of technology

It achieves the long-lasting effect of antibacterial, anti-mold and TVOC removal in adhesives. The ingredients are safe and environmentally friendly, and have no toxic decomposition products and are not irritating to the human body.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GHA0000008937620000061
    Figure GHA0000008937620000061
Patent Text Reader

Abstract

The present application relates to the field of chitosan-modified additives, and specifically discloses a multifunctional additive for adhesives and a preparation method thereof, wherein the multifunctional additive for adhesives comprises the following raw materials in parts by weight: 10-20 parts of zinc-based chitosan slow-release particles, 5-13 parts of deodorants, 8-18 parts of antibacterial agents, and 40-70 parts of water; the zinc-based chitosan slow-release particles are prepared by the following steps: mixing aldehyde-modified cyclodextrin with chitosan glue, adding a catalyst, reacting to obtain cyclodextrin-grafted chitosan, and reacting with a soluble zinc salt to obtain zinc-based chitosan slow-release particles. The preparation method of the multifunctional additive for adhesives comprises the following steps: uniformly mixing zinc-based chitosan slow-release particles, deodorants, antibacterial agents, and water to obtain an additive. The obtained additive has excellent antibacterial, mildew-proof, and TVOC removal properties for use in adhesives, and its effectiveness is long-lasting, its ingredients are safe and environmentally friendly, and it has no toxic decomposition products and is non-irritating to the human body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of adhesive additives, and more specifically, to a multifunctional additive for adhesives and a preparation method thereof. Background Art

[0002] At present, common antibacterial agents, mildew inhibitors or formaldehyde removal preparations on the market, such as quaternary ammonium salts, phenol ethers, organic metals, zinc salts, etc., although these preparations can play a certain antibacterial, mildew-proof, formaldehyde removal and other effects, but the effective time of the relevant preparations added to adhesives is short, and the decomposition products of some preparations are toxic, which is not conducive to long-term contact with the human body. Summary of the invention

[0003] The present application provides a multifunctional additive for adhesives and a preparation method thereof. The obtained additive can maintain excellent antibacterial, anti-mildew and TVOC removal properties when used in adhesives, has long-lasting effects, is safe and environmentally friendly in ingredients, has no toxic decomposition products, and is non-irritating to the human body.

[0004] In the first aspect, the present application provides a multifunctional additive for adhesives using the following technical scheme: a multifunctional additive for adhesives, comprising the following raw materials in parts by weight: 10-20 parts of zinc-based chitosan sustained-release particles, 5-13 parts of deodorant, 8-18 parts of antibacterial agent, and 40-70 parts of water;

[0005] The zinc-based chitosan sustained-release particles are prepared by the following steps: mixing aldehyde-modified cyclodextrin with chitosan glue, adding a catalyst, reacting to obtain cyclodextrin-grafted chitosan, and finally reacting with a soluble zinc salt to obtain zinc-based chitosan sustained-release particles.

[0006] Furthermore, the preparation step of chitosan glue is: dissolving chitosan in an acidic solution to obtain chitosan glue.

[0007] Furthermore, the acidic solution may be a hydrochloric acid solution or an acetic acid solution.

[0008] As a further preferred embodiment of the acidic solution, the acidic solution is preferably an acetic acid solution, and the mass concentration of the acetic acid solution is 1-5%. The acetic acid solution is widely available, cheap and easy to obtain, and can reduce the cost of the enterprise.

[0009] Furthermore, the deacetylation degree of chitosan is 80-90%, which ensures the excellent solubility of chitosan.

[0010] By adopting the above technical scheme, the aldehyde-modified cyclodextrin contains aldehyde groups, and the chitosan glue treated with an acidic solution can react with the aldehyde-modified cyclodextrin. Under the action of a catalyst, the cyclodextrin is grafted onto the chitosan through a Schiff base reaction, and finally reacts with a soluble zinc salt, which can have an excellent coating and protection effect on zinc ions, forming an inclusion complex with a special structure, thereby improving the stability of zinc ion release in a weakly alkaline or alkaline environment, and enabling the product to maintain excellent and lasting antibacterial and antifungal properties during use.

[0011] Antimicrobial agents can effectively inhibit bacterial growth. When combined with zinc-based chitosan slow-release particles, they can further enhance the antimicrobial and mildew-proof effects of the product, continuously release active ingredients for a long time, and have lasting antimicrobial and mildew-proof functions. Deodorants can effectively remove volatile organic compounds and reduce the impact of TVOC on the human body.

[0012] Preferably, the aldehyde-modified cyclodextrin is prepared by the following steps: hydroxypropyl-β-cyclodextrin and an oxidant are mixed and reacted in a mass ratio of (2-10):1 to obtain the aldehyde-modified cyclodextrin.

[0013] By adopting the above technical scheme, hydroxypropyl-β-cyclodextrin, as a cyclic oligosaccharide derivative, has a hollow cylindrical three-dimensional ring structure and certain pores in its molecules. After being grafted with chitosan, it can form a special structure inclusion complex with zinc ions, etc., which has an excellent coating and protection effect on zinc salts and can improve the stability of zinc ion release, so that the product maintains excellent and lasting antibacterial and anti-mildew properties during use.

[0014] Preferably, the mass ratio of the aldehyded cyclodextrin to the chitosan glue is 1:(3-5).

[0015] By adopting the above technical solution, the dosage relationship of aldehyde-modified cyclodextrin and chitosan glue is optimized, and the grafting rate of cyclodextrin is improved. Through research experiments, it is found that when the mass ratio of aldehyde-modified cyclodextrin to chitosan glue is 1:(3-5), the quality of the product is better.

[0016] Preferably, the mass ratio of cyclodextrin grafted chitosan to soluble zinc salt is 1:(0.1-0.3).

[0017] Optimizing the dosage relationship between cyclodextrin grafted chitosan and soluble zinc salt, when the mass ratio of cyclodextrin grafted chitosan to soluble zinc salt is 1:(0.1-0.3), it can not only improve the stability of zinc ion release in weak alkaline or alkaline environment, but also further improve the antibacterial and mildew-proof properties of the product during use. In terms of the dosage of soluble zinc salt, excessive dosage of soluble zinc salt is likely to cause precipitation or floccules in the system, while too little dosage of soluble zinc salt cannot achieve effective antibacterial and mildew-proof effects.

[0018] Preferably, the catalyst is one of glacial acetic acid, ammonia water and sodium hydroxide.

[0019] Furthermore, the catalyst is preferably glacial acetic acid.

[0020] By adopting the above technical solution and selecting a suitable catalyst, the grafting of chitosan to cyclodextrin is promoted and the grafting rate is increased, thereby further ensuring the product quality.

[0021] Preferably, the soluble zinc salt is one or more of zinc sulfate, zinc acetate and zinc nitrate. The soluble zinc salt can be zinc sulfate, zinc acetate, a compound of zinc acetate and zinc nitrate, or a compound of zinc nitrate and zinc sulfate.

[0022] Preferably, the antibacterial agent is mainly one of polyhexamethyleneguanidine hydrochloride, polyhexamethylene biguanidine phosphate and polyhexamethyleneguanidine sulfate.

[0023] Preferably, the deodorant is one or both of phytoncide and zinc ricinoleate.

[0024] By adopting the above technical scheme, the soluble zinc salts have excellent solubility and can provide zinc ions for the system. Under the action of cyclodextrin-grafted chitosan, the stability of zinc ion release in a weakly alkaline or alkaline environment can be improved, so that the product maintains excellent and lasting antibacterial and antifungal properties during use. The antibacterial agent uses guanidine salts, which have high activity. The polymer is positively charged, and most bacteria are generally negatively charged. The use of guanidine salts can effectively adsorb bacteria and cause them to inactivate, playing an excellent antibacterial role. Phytoncide and zinc ricinoleate can effectively adsorb macromolecular substances, have excellent effects in removing formaldehyde and sulfur-containing compounds, and have good deodorizing effects.

[0025] Preferably, the oxidant is one of p-toluenesulfonyl chloride, 2,2,6,6-tetramethylpiperidine nitrogen oxide, and o-iodoylbenzoic acid.

[0026] By adopting the above technical solution, the component selection of the oxidant is optimized to facilitate the aldehyde modification of hydroxypropyl-β-cyclodextrin.

[0027] In a second aspect, the present application provides a method for preparing a multifunctional additive for an adhesive, using the following technical solution:

[0028] A method for preparing a multifunctional additive for adhesives comprises the following steps: uniformly mixing zinc-based chitosan slow-release particles, a deodorant, an antibacterial agent and water to obtain the additive.

[0029] By adopting the above technical scheme, zinc-based chitosan slow-release particles, deodorizers, antibacterial agents and water are uniformly mixed to obtain an additive, which can be widely used in adhesives and then used in the manufacture of surface paper impregnation and artificial board veneer impregnation, so that the product can maintain excellent antibacterial, anti-mildew and TVOC removal properties, and the effectiveness can be long-lasting.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. Chitosan is selected and effectively grafted with cyclodextrin, and is combined with an antibacterial agent and a deodorant with a guanidine structure. The components work together to more effectively prevent the infection and survival of bacteria and molds. At the same time, it is also antibacterial, mildew-proof, safe and environmentally friendly, non-irritating to the human body, and has no toxic decomposition products. The obtained additive has excellent performance and can be widely used in adhesives and widely used in the impregnation of facing paper for artificial boards.

[0032] 2. When the additives of the present application are used in adhesives, the amount of the additives added is generally 2%-4%, which is lower than the amount of ordinary commercially available additives. While reducing the amount of additives, the present application can also enable the facing paper or the artificial board pressed with the facing paper to achieve excellent antibacterial, mildew-proof, and TVOC removal effects, and the antibacterial and mildew-proof properties are durable. DETAILED DESCRIPTION

[0033] The embodiments of the present invention will be described in detail below in conjunction with examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention. The specific conditions not specified in the examples are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0034] Preparation Example of Zinc Chitosan Sustained Release Granules

[0035] Preparation Example 1

[0036] Zinc chitosan sustained-release granules are prepared by the following steps:

[0037] Dissolve chitosan with a deacetylation degree of 80% in a hydrochloric acid solution with a mass concentration of 1%, and stir until transparent to obtain chitosan glue;

[0038] Hydroxypropyl-β-cyclodextrin and p-toluenesulfonyl chloride are mixed and reacted in a mass ratio of 2:1 to obtain aldehyde-modified cyclodextrin; the aldehyde-modified cyclodextrin and chitosan glue are mixed in a mass ratio of 1:3, and ammonia water is added to react to obtain cyclodextrin-grafted chitosan; the cyclodextrin-grafted chitosan is mixed with a soluble zinc salt in a mass ratio of 1:0.3, and the soluble zinc salt is zinc acetate and zinc nitrate in a mass ratio of 1:1, and the reaction is stirred for 1 hour to obtain zinc-based chitosan sustained-release particles.

[0039] Preparation Example 2

[0040] Zinc chitosan sustained-release granules are prepared by the following steps:

[0041] Dissolving chitosan with a deacetylation degree of 90% in an acetic acid solution with a mass concentration of 5%, stirring until transparent, to obtain chitosan glue;

[0042] The hydroxypropyl-β-cyclodextrin and o-iodoxybenzoic acid are mixed and reacted at a mass ratio of 10:1 to obtain aldehyde-modified cyclodextrin;

[0043] The aldehyde-modified cyclodextrin and chitosan gel were mixed at a mass ratio of 1:5, sodium hydroxide was added, and the reaction was performed to obtain cyclodextrin-grafted chitosan. The cyclodextrin-grafted chitosan was mixed with zinc sulfate at a mass ratio of 1:0.1, and the reaction was stirred for 4 hours to obtain zinc-based chitosan sustained-release particles.

[0044] Preparation Example 3

[0045] Zinc chitosan sustained-release granules are prepared by the following steps:

[0046] Dissolving chitosan with a deacetylation degree of 85% in an acetic acid solution with a mass concentration of 3%, stirring until transparent, to obtain chitosan glue;

[0047] The hydroxypropyl-β-cyclodextrin and 2,2,6,6-tetramethylpiperidinium N-oxide are mixed and reacted in a mass ratio of 5:1 to obtain aldehyde-modified cyclodextrin;

[0048] The aldehyde-modified cyclodextrin and chitosan glue were mixed in a mass ratio of 1:4, glacial acetic acid was added, and the cyclodextrin-grafted chitosan was obtained. The cyclodextrin-grafted chitosan was mixed with zinc nitrate in a mass ratio of 1:0.2, and the reaction was stirred for 3 hours to obtain zinc-based chitosan sustained-release particles.

[0049] Preparation Example 4

[0050] Zinc chitosan sustained-release granules are prepared by the following steps:

[0051] Dissolve chitosan with a deacetylation degree of 70% in an acetic acid solution with a mass concentration of 4%, and stir until transparent to obtain a chitosan glue solution;

[0052] Hydroxypropyl-β-cyclodextrin and o-iodoxybenzoic acid are mixed and reacted in a mass ratio of 5:2 to obtain aldehyde-modified cyclodextrin; the aldehyde-modified cyclodextrin and chitosan glue are mixed in a mass ratio of 1:2, glacial acetic acid is added to react to obtain cyclodextrin-grafted chitosan, the cyclodextrin-grafted chitosan is mixed with zinc acetate in a mass ratio of 1:0.5, and the reaction is stirred for 3 hours to obtain zinc-based chitosan sustained-release particles.

[0053] Example

[0054] Example 1

[0055] A multifunctional additive for an adhesive is prepared by uniformly mixing 10 parts of zinc-based chitosan sustained-release particles obtained in Preparation Example 1, 13 parts of phytoncide, 8 parts of polyhexamethylene biguanide phosphate, and 40 parts of water.

[0056] Example 2

[0057] A multifunctional additive for an adhesive is prepared by uniformly mixing 20 parts of the zinc chitosan sustained-release particles obtained in Preparation Example 2, 2 parts of phytoncides, 3 parts of zinc ricinoleate, 18 parts of polyhexamethylene guanidine sulfate, and 70 parts of water.

[0058] Example 3

[0059] A multifunctional additive for an adhesive is prepared by uniformly mixing 15 parts of the zinc-based chitosan sustained-release particles obtained in Preparation Example 2, 7 parts of phytoncide, 12 parts of polyhexamethylene guanidine hydrochloride, and 66 parts of water.

[0060] Example 4

[0061] The difference from Example 3 is that the zinc-based chitosan sustained-release particles obtained in Preparation Example 3 are used, and the rest are the same as Example 3.

[0062] Example 5

[0063] The difference from Example 3 is that the zinc-based chitosan sustained-release particles obtained in Preparation Example 4 are selected, and the rest are the same as Example 3.

[0064] Comparative Example

[0065] Comparative Example 1

[0066] The difference from Example 4 is that

[0067] The preparation steps of zinc chitosan sustained-release granules are as follows:

[0068] Dissolving chitosan with a deacetylation degree of 85% in an acetic acid solution with a mass concentration of 3%, stirring until transparent, to obtain chitosan glue;

[0069] The chitosan gel solution and zinc sulfate are mixed in a mass ratio of 1:4:0.2 to obtain zinc-based chitosan sustained-release particles;

[0070] The rest are the same as in Example 4.

[0071] Comparative Example 2

[0072] The difference from Example 4 is that the zinc-based chitosan sustained-release particles are replaced by zinc-based sustained-release particles in equal amounts, wherein the preparation steps of the zinc-based sustained-release particles are as follows:

[0073] The hydroxypropyl-β-cyclodextrin and 2,2,6,6-tetramethylpiperidinium N-oxide are mixed and reacted in a mass ratio of 5:1 to obtain aldehyde-modified cyclodextrin;

[0074] The aldehyde-modified cyclodextrin and zinc sulfate are uniformly mixed in a mass ratio of 1:0.2 to obtain zinc-based particles;

[0075] The rest are the same as in Example 4.

[0076] Comparative Example 3

[0077] The difference from Example 4 is that 5 parts of hydroxypropyl-β-cyclodextrin, 10 parts of chitosan, 7 parts of phytoncide, 12 parts of polyhexamethyleneguanidine hydrochloride and 66 parts of water are uniformly mixed to obtain the additive.

[0078] Comparative Example 4

[0079] The difference from Example 4 is that an equal amount of polyhexamethyleneguanidine hydrochloride is replaced by a quaternary ammonium salt, and the rest is the same as Example 4.

[0080] Comparative Example 5

[0081] The difference from Example 4 is that no phytoncide is added, and the rest is the same as Example 4.

[0082] Performance testing

[0083] Detection method / test method

[0084] The additives obtained in Examples 1-5 and Comparative Examples 1-5 were uniformly mixed with melamine glue, with the additive added in an amount of 3% to obtain melamine glue samples. Each melamine glue sample was used to produce impregnated paper, which was then pressed onto formaldehyde-free boards from the same batch to obtain melamine boards.

[0085] The triamine board samples obtained in Examples 1-5 and Comparative Examples 1-5 were tested for antibacterial properties against Escherichia coli and Staphylococcus aureus and antibacterial durability according to JC / T2039-2010 "Antibacterial and Mildew-Proof Wood Decorative Panels", and the mildew resistance grade and mildew resistance durability were tested. The TVOC removal performance was measured according to QB / T2761-2006 "Method for Determination of Purification Effect of Indoor Air Purification Products", and the results are recorded in Table 1.

[0086] Table 1 Test results

[0087]

[0088]

[0089] From Examples 1-5 and Table 1, it can be seen that the additive obtained by using the specific formula of the present application can maintain excellent antibacterial, anti-mildew and TVOC removal properties when used in adhesives, with long-lasting effects, safe and environmentally friendly ingredients, no toxic decomposition products, and no irritation to the human body.

[0090] Combining Example 4 and Comparative Examples 1-3 and Table 1, it can be seen that comparative example 1 lacks aldehyde-formyl cyclodextrin, comparative example 2 lacks chitosan glue, comparative example 3 lacks zinc salt and chitosan is not grafted and modified, and the additives obtained in comparative examples 1-3 are used in triamine glue, and the antibacterial and mildew-proof properties are significantly reduced, and the standards of antibacterial persistence and mildew-proof persistence cannot be met. This is because the chitosan glue after acid solution treatment can react with aldehyde-formyl cyclodextrin, under the action of a catalyst, through a Schiff base reaction, cyclodextrin is grafted onto chitosan, and finally reacts with a soluble zinc salt, which can play an excellent coating and protection role on zinc ions, forming a special structure inclusion complex, improving the stability of zinc ions released in a weakly alkaline or alkaline environment, and cooperating with an antibacterial agent and a deodorant, so that the product can maintain excellent and lasting antibacterial and mildew-proof properties during use, and has good performance in removing TVOC.

[0091] Combining Example 4 and Comparative Examples 4-5 and Table 1, it can be seen that in Comparative Example 4, quaternary ammonium salt is used as an antibacterial agent, and in Comparative Example 5, phytoncide is lacking. The additives obtained in Comparative Examples 4 and 5 are used in triamine glue, and the antibacterial and mildew-proof properties and TVOC removal are not good, and the antibacterial and mildew-proof durability are also significantly reduced. After using guanidine salts with guanidine structure as antibacterial agents and phytoncide as deodorants, and compounding with zinc-based chitosan slow-release particles, the components can cooperate with each other, more effectively preventing the infection and survival of bacteria and molds, effectively improving the antibacterial, mildew-proof, and TVOC removal properties of the product, and the effect is long-lasting.

[0092] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A multifunctional additive for adhesives, characterized in that: The invention comprises the following raw materials in parts by weight: 10-20 parts of zinc-based chitosan slow-release particles, 5-13 parts of deodorant, 8-18 parts of antibacterial agent and 40-70 parts of water; the zinc-based chitosan slow-release particles are prepared by the following steps: mixing aldehyde-modified cyclodextrin with chitosan glue, adding a catalyst, reacting to obtain cyclodextrin-grafted chitosan, and finally reacting with a soluble zinc salt to obtain zinc-based chitosan slow-release particles; the aldehyde-modified cyclodextrin is prepared by the following steps: mixing hydroxypropyl-β-cyclodextrin and an oxidant at a mass ratio of (2-10):1 to obtain aldehyde-modified cyclodextrin; the antibacterial agent is one or two of polyhexamethyleneguanidine hydrochloride, polyhexamethylene biguanide phosphate and polyhexamethyleneguanidine sulfate; the deodorant is one or two of phytoncide and zinc ricinoleate.

2. The multifunctional additive for adhesive according to claim 1, characterized in that: The mass ratio of the aldehyde-modified cyclodextrin to the chitosan glue is 1:(3-5).

3. The multifunctional additive for adhesive according to claim 1 or 2, characterized in that: The mass ratio of the cyclodextrin grafted chitosan to the soluble zinc salt is 1:(0.1-0.3).

4. The multifunctional additive for adhesive according to claim 3, characterized in that: The catalyst is one of glacial acetic acid, ammonia water and sodium hydroxide.

5. The multifunctional additive for adhesive according to claim 1, characterized in that: The soluble zinc salt is one or more of zinc sulfate, zinc acetate and zinc nitrate.

6. The multifunctional additive for adhesive according to claim 1, characterized in that: The oxidant is one of p-toluenesulfonyl chloride, 2,2,6,6-tetramethylpiperidine nitrogen oxide, and o-iodoacylbenzoic acid.

7. A method for preparing a multifunctional additive for adhesives according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing zinc-based chitosan slow-release particles, a deodorant, an antibacterial agent and water to obtain an additive.

Citation Information

Patent Citations

  • KR20220090726A